Patients' Expectations Before Initiation of Intrathecal Baclofen Treatment: A Longitudinal Study with 1-Year Follow-Up - Stina Gunnarsson; Dag Lemming; Siw Alehagen; Tommy Bergenheim; Björn Gerdle; Kersti Samuelsson (Medical Journals Sweden, 2023)
Objective: To investigate patients' expectations, met/unmet expectations and satisfaction with intrathecal baclofen treatment in relation to effect on spasticity, pain intensity, sleep quality, occupational performance, well-being and self-efficacy. Design: A prospective longitudinal study with follow-up at 1 year. Patients: Consecutive patients, age ≥ 18 years with a disabling spasticity of cerebral or spinal origin selected for intrathecal baclofen treatment at 2 university hospitals in Sweden were included. From August 2016 to June 2019, 35 patients began intrathecal baclofen treatment; 29 patients were included and completed the study. Methods: Baseline and 1-year follow-up included assessment of spasticity by physiotherapists, a semi-structured interview regarding occupational performance using the Canadian Occupational Performance Measure and a questionnaire. Results: Overall satisfaction with treatment and satisfaction with occupational performance were reported as moderate. Important variables that explained satisfaction with occupational performance were improvements in performance, expectations and performance before treatment. Patients had higher expectations compared with the 1-year outcomes regarding occupational performance, spasticity, pain intensity and sleep quality, although improvements were reported. Conclusion: A thorough discussion of goal setting with intrathecal baclofen treatment before implantation is necessary to give patients individual and realistic expectations. LAY ABSTRACT Spasticity is a common complication for patients with various neurological conditions, such as spinal cord injury, acquired brain injury, cerebral palsy and multiple sclerosis. For patients with disabling spasticity, intrathecal baclofen is an effective and satisfactory treatment. Dissatisfaction with treatment has been described, but has not been thoroughly evaluated. Therefore, this study examined patients' expectations of effects on occupational performance, spasticity, pain intensity and sleep quality. Patients were followed-up after 1 year on the treatment, and results and satisfaction were reported. Patients improved, but not as much as they had expected. As a group, they were moderately satisfied, and important variables for satisfaction were found to be improvements in performance, expectations and initial performance. These results highlight the need to discuss patients' expectations and goals with this treatment even more thoroughly and to address realistic expectations.